2017
DOI: 10.1002/14651858.cd011802.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Stepping down the dose of inhaled corticosteroids for adults with asthma

Abstract: The strength of the evidence is not sufficient to determine whether stepping down the dose of ICS is of net benefit (in terms of fewer adverse effects) or harm (in terms of reduced effectiveness of treatment) for adult patients with well-controlled asthma. A small number of relevant studies and varied outcome measures limited the number of meta-analyses that we could perform. Additional well-designed RCTs of longer duration are needed to inform clinical practice regarding use of a 'stepping down ICS' strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Rank et al reported that withdrawing low‐dose ICS was associated with a higher risk of exacerbations, which occurred in 38% of those patients over a mean period of 6 months. In contrast, Hagan et al suggested that reducing ICS to a lower dose did not increase the risk of asthma exacerbations while in a recent article, Crossingham et al concluded that the body of evidence was insufficient to draw conclusions about the risks and benefits of stepping‐down ICS. In these studies, the prevalence of exacerbations was 21% and 18%, respectively, over a mean follow‐up of 5‐6 months in patients whose ICSs were reduced.…”
Section: Discussionmentioning
confidence: 97%
“…Rank et al reported that withdrawing low‐dose ICS was associated with a higher risk of exacerbations, which occurred in 38% of those patients over a mean period of 6 months. In contrast, Hagan et al suggested that reducing ICS to a lower dose did not increase the risk of asthma exacerbations while in a recent article, Crossingham et al concluded that the body of evidence was insufficient to draw conclusions about the risks and benefits of stepping‐down ICS. In these studies, the prevalence of exacerbations was 21% and 18%, respectively, over a mean follow‐up of 5‐6 months in patients whose ICSs were reduced.…”
Section: Discussionmentioning
confidence: 97%
“…Two Cochrane reviews found insufficient trial evidence regarding step down of ICS or long-acting beta agonists (LABA). 16,17 Participants in our study used a variety of approaches to step down, reducing both ICS and LABA or just ICS; with even less concord for patients with an additional asthma therapy. Moreover, there was no consensus as to how to identify suitable patients.…”
Section: Discussionmentioning
confidence: 99%
“…65 Comparing those who stepped down with controls, no significant differences were found for several outcomes including needing oral corticosteroid (odds ratio 1.31, 0.82 to 2.08), hospital admission (4.06, 0.45 to 36.9), or all cause serious adverse events (0.60, 0.11 to 3.33). 31 The odds ratio of 4 for hospital admission may be clinically relevant; however, owing to the limited number of events and high level of imprecision, this result should be interpreted with caution.…”
Section: Substitution Of Leukotriene Receptor Antagonists For Inhaledmentioning
confidence: 95%